The Determinants of Environmental Disclosure in Indonesia, Malaysia, and Thailand - Safitri, Lisdiana; Sri Wahyuningrum, Indah Fajarini (Accounting Analysis Journal, 2021)
The study aims to analyze the affecting factors of environmental disclosure, such as company size, industry type, profitability, company age, environmental performance, and institutional ownership. The population of this study is the manufacturing companies listed on Indonesia Stock Exchange (IDX), Kuala Lumpur Stock Exchange (KLSE), and Stock Exchange Thailand (SET) in 2019. The sampling technique uses purposive sampling with 93 companies. The analysis technique uses is multiple linear regression. The result of this study show company size, environmental performance, and institutional ownership have a positive and significant effect on environmental disclosure. On the other side, this result shows industry type, profitability, and company age have an insignificant effect on environmental disclosure. The conclusion of this study is the company which is categorized as the bigger company with many institutions ownership, with verification ISO 14001 has more responsibility to contribute to environmental disclosure. This is because the company has operational activities and impacts related to the environment. Keywords: Environmental Disclosure; Company Size; Industry Type; Profitability; Company Age; Environmental Performance